Stable protein-repellent zwitterionic polymer brushes grafted from silicon nitride - Nguyen, Ai T (Langmuir : the ACS journal of surfaces and colloids, 2011)
Zwitterionic poly(sulfobetaine acrylamide) (SBMAA) brushes were grafted from silicon-rich silicon nitride (SixN4, x > 3) surfaces by atom transfer radical polymerization (ATRP) and studied in protein adsorption experiments. To this aim ATRP initiators were immobilized onto SixN4 through stable Si-C linkages via three consecutive reactions. A UV-induced reaction of 1,2-epoxy-9-decene with hydrogen-terminated SixN4 surfaces was followed by conversion of the epoxide with 1,2-ethylenediamine resulting in primary and secondary amine-terminated surfaces. A reaction with 2-bromoisobutyryl bromide led to ATRP initiator-covered surfaces. Zwitterionic polymer brushes of SBMAA were grown from these initiator-coated surfaces (thickness ∼30 nm), and the polymer-coated surfaces were characterized in detail by static water contact angle measurements, X-ray photoelectron spectroscopy (XPS), and an atomic force microscope (AFM). The adsorption of proteins onto zwitterionic polymer coated surfaces was evaluated by in situ reflectometry, using a fibrinogen (FIB) solution of 0.1 g·L(-1), and compared to hexadecyl-coated SixN4 surfaces (C16-SixN4), uncoated air-based plasma oxidized SixN4 surfaces (SiOy-SixN4), and hexa(ethylene oxide)-coated SixN4 surfaces (EO6-SixN4). Excellent protein repellence (>99%) was observed for these zwitterionic polymer-coated SixN4 surfaces during exposure to FIB solution as compared to C16-SixN4 surfaces. Furthermore, the stability of these zwitterionic polymer-coated SixN4 surfaces was surveyed by exposing the surfaces for 1 week to phosphate buffered saline (PBS) solution at room temperature. The zwitterionic polymer-coated SixN4 surfaces before and after exposure to PBS solution were characterized by XPS, AFM, and water contact angle measurements, and their protein-repelling properties were evaluated by reflectometry. After exposure to PBS solution, the zwitterionic polymer coating remained intact, and its thickness was unchanged within experimental error. No hydrolysis was observed for the zwitterionic polymer after 1 week exposure to PBS solution, and the surfaces still repelled 98% FIB as compared to C16-SixN4 surfaces, demonstrating the long-term efficiency of these easily prepared surface coatings